Antibiotics and resistant genes in the gut of Chinese nine kinds of freshwater or marine fish. Issue 4 (3rd April 2022) - Li, Wenpeng; Niu, Zhiguang; Zhang, Xiaohan; Zhang, Kai; Luo, Susu
Abstract: Antibiotic resistance genes (ARGs) may lead to bacterial resistance and using antibiotics will promote ARGs spread. Large amounts of antibiotics were used in aquaculture, but little attention was paid to the antibiotic resistant in fish gut. In this study, nine kinds of Chinese freshwater and marine fish were acquired in a city of northern China to test the amount of antibiotics and ARGs residues in their intestinal contents. The results showed that 4 kinds of antibiotics were detected from the intestinal contents, including Doxycycline (DOX), Tetracycline (TC), Sulfamethoxazole (SMX) and Roxithromycin (ROX), and the antibiotics with the largest detected amount was ROX in Sardinops sagax (2.83 μg kg −1 ). Ten kinds of ARGs were detected from the intestinal contents, including str A, str B, erm B, bla TEM, oxa -30, qnr B, qnr D, sul 1, sul 2 and tet B, as well as one type of integron intI 1. The most abundant ARGs were bla TEM . Correlation analysis showed huge difference between freshwater fish and marine fish. The results can improve our understanding of the antibiotics and ARGs residues in edible fish.